Optimization Analysis of Excavation Procedure Design of Underground Powerhouses under High In Situ Stress in China - Xiao Liu (MDPI AG, 2021)
To recommend the excavation procedures and design parameters for underground powerhouses, excavation procedures of fifty-one underground powerhouses in China were summarized and analyzed based on in situ stress conditions. Firstly, the complex stress environment in China was introduced and fifty-one underground powerhouses with their engineering scale, size, lithology, rock classification and in situ stress level were listed in detail. Subsequently, to evaluate the influence of in situ stress levels on excavation procedure design, the correlation between excavation procedures and in situ stress level in three main excavation zones were analyzed accordingly. Moreover, to provide the excavation design recommendations, the strength–stress ratio (SSR) was promoted to analyze and recommend the design parameters, and the blasting excavation design based on the stress transient unloading control was also supplemented. The results show that excavation procedures have different priorities under different in situ stress levels, and the design parameters show an obvious relationship with in situ stress levels. Moreover, the excavation procedure parameters are suggested to adjust accordingly under different SSR. The discussion of influencing factors and specification ensures its rationality and accuracy. It is believed that the summary and recommendations can provide a good reference for excavation procedure optimization of underground powerhouse under high in situ stress.